Environmentalism with Chinese Characteristics—A Review of Matthew E. Kahn and Siqi Zheng’s Blue Skies over Beijing: Economic Growth and the Environment in China - Coxhead, Ian (Journal of Economic Literature, 2019)
China’s dramatic rise from poverty to global economic prominence has been accompanied by an equally dramatic increase in environmental damages. The book under review presents an exploration of economic and political economy factors that might bring about a reversal in emissions that contribute to high pollution loadings in large urban areas. The authors highlight preference shifts associated with rapid growth of per capita income and express optimism about government responses to demands for a cleaner environment. There are some indications that China’s largest cities are indeed getting cleaner air. However, total emissions (largely from heavy industry and coal-fired energy generators) continue to rise, and the mechanisms by which preference shifts turn into policy changes remain opaque. It may be that China’s most polluting industries are sorting into localities where either preferences for clean air are less pronounced or local governments are less responsive. This may match a positively selected counterflow of individuals seeking better environmental amenities and more responsive government. (JEL O13, O44, P28, Q53, Q56, Q58)